Memupuk Minat Baca Anak - Pranandia Popi Pitaloka (UIN Sumatera Utara, 2018)
This article discusses about fostering children's reading interest. The research method used is, looking for sources in the library (Library Research), Observation (Observation), and question and answer (Questionnaire). School libraries can be used as a source of learning for students, both in the process of teaching and learning activities in formal and non-formal ways to help schools in their efforts to achieve educational goals in the school. If the teacher's high reading interest will be easier and lighter in carrying out his duties. Children will be more active, seek and explore knowledge. Keywords: reading interest, children, school library